Decreasing the Uterine Blood Flow with Electroacupuncture: Bidermatomal and Monodermatomal Applications - YOLDEMİR, AHMET TEVFİK (KARGER, 2017)
Background: Previously we demonstrated a uterine fibroma case in which the decrease in the uterine artery blood flow was obtained with bidermatomal electroacupuncture (EA). A prospective study was conducted to validate the efficacy of bidermatomal and monodermatomal EA applications. Methods: Ten healthy women participated 3 times for 3 steps of the study. Each woman enrolled into a bidermatomal sham control group application, a bidermatomal 80 Hz EA and as a last step, a monodermatomal EA with 80 Hz. Color Doppler ultrasonographic recordings were made to detect baseline blood flow parameters by a pulsatility index (PI), volume flow, area and diameter of each uterine artery and after stimulations. Results: Doppler ultrasonographic recordings demonstrated statistically significant decreases of the blood flow both with bidermatomal (p = 0.03 for the left side PI and p = 0.04 for the right side PI) and monodermatomal EA (p = 0.006 for the left PI and p = 0.002 for the right side PI). The sham control group did not show a significant change in blood flow parameters. Conclusions: The present study validates the efficacy of the bidermatomal but also the monodermatomal EA with 80 Hz on decreasing the blood flow to the uterus. (C) 2016 S. Karger AG, Basel
Keywords: Neuromodulation; Artery; Blood flow; Electroacupuncture; Electrostimulation; ANESTHETIZED RATS; MENSTRUAL-CYCLE; STIMULATION; ARTERY; FREQUENCY; IMPEDANCE